Pengembangan Media Pembelajaran Quizwhizzer: Inovasi Interaktif untuk Meningkatkan Efektivitas Pembelajaran IPA - Putri, Frysca Amanda; Insani, Galuh Nur; Khoirunnisa, Salwa Cantika; Rostika , Deti; Sudarmansyah, Ranu (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Technology has become a crucial element in education, as evidenced by the emergence of various applications that support the learning process. One example of such applications is interactive games that use information and communication technology. In learning Natural Sciences (IPA), students often only follow the teacher's direction and use books as references, causing passive learning in the classroom. The main objective of this research is to explore and find out the application of Quizwhizzer learning media in science learning process. This research uses a qualitative method of literature study to analyze current sources of information. The research problem involves aspects such as network stability and potential student cheating that can affect the effectiveness of using Quizwhizzer. The results showed that the use of Quizwhizzer can increase student engagement behaviorally, emotionally, and cognitively, and provide positive results in student achievement. Nonetheless, the study also identified some drawbacks, such as network instability and potential student cheating. The conclusion of this study provides an in-depth look at the benefits and challenges of using Quizwhizzer in interactive learning, with implications for educators and educational technology developers to improve the learning experience through innovation and problem solving found